Household waste management in Oum El Bouaghi: inventory, challenges and development prospects - SAKER, Soumia; ALKAMA, ALKAMA (Journal of Human Sciences, 2020)
Oum El Bouaghi is suffering from many economic , social and environmental issues which bather both its residents and the local authorities .This problem is certainly due to the waste and trash that are thrown every day by the inhabitants. There should be an urgent solution as a sustainable local development to face this disastrous situation. Wastes are increasing day by day and impacts all of us .We are all upset about this current terrible situation in our hometown .Our role is to look for an efficient rational plan to cope with this problem and lead it effectively. Our research aims to look for good analyses for Waste management system to get used very well and understand the reality of this situation and suggest effective solutions that fit both the urban and cultural context by collaborating and sharing the work and be more aware about the latter. The establishment of a rigorous process and the use of adequate methods should raise the public awareness of the issues of household waste management, and therefore lead them to adopt a responsible and citizen behavior